Docile Object and Proposing Object: : a study on the qualities of the object and its possibilities in the creative process in Performing Arts - Della Costa, Rossana; Rossini, Élcio (Revista Brasileira de Estudos da Presença, 2022)
This article develops, identifies and presents two qualities to think about the objects used in creation processes in Performing Arts, in which we investigate body-object relations. We present the objects as docile or proposing and discuss their respective characteristics. Our methodology involved the selection and analysis of contemporary works in which we could examine principles relating to the physical characteristics of materials as well as the approaches adopted by the body in its relation to the object. This article is inspired by the Foucauldian notion of displacement applied to the consideration of other ways of thinking about the object beyond the so-called theater of objects or the understanding of the object as a scenic prop. In conclusion, we argue that recognizing these qualities of the object can contribute to expand the uses of the object in creation processes, including the production of specific objects for the Performing Arts.